2022
DOI: 10.1002/aenm.202201114
|View full text |Cite
|
Sign up to set email alerts
|

Contact Resistance of Carbon–Lix(Ni,Mn,Co)O2 Interfaces

Abstract: Electronic resistance in lithium‐ion battery positive electrodes is typically attributed to the bulk resistance of the active material and the network resistance of the carbon additive. Expected overpotentials from these bulk components are minimal relative to that from charge‐transfer resistance. However, literature reports show that cell overpotentials are often much more sensitive to conductive additives than the expected level from bulk or percolating‐network transport. This discrepancy motivated a detaile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The voltage cutoffs were set at 2 and 4 V. Two-electrode tests were performed by an Arbin LBT20084 battery cycler or a Biologic BCS-805. Three-electrode cells were fabricated as detailed in Kuo et al Three-electrode measurements were performed using a Biologic MPG-2.…”
Section: Methodsmentioning
confidence: 99%
“…The voltage cutoffs were set at 2 and 4 V. Two-electrode tests were performed by an Arbin LBT20084 battery cycler or a Biologic BCS-805. Three-electrode cells were fabricated as detailed in Kuo et al Three-electrode measurements were performed using a Biologic MPG-2.…”
Section: Methodsmentioning
confidence: 99%
“…3d and e) is estimated as the voltage difference between NMC622 samples (CB, CB-OH (24 h), CB]O (72 h), and CB-COOH (20%) at 0.25C) with CB (at 0.05C), and thus is termed overpotential. 73 In Fig. 3c, the GCD curve of NMC622 with CB at 0.05C (discharge capacity ∼175 mA h g −1 ) is shown as reference.…”
Section: Electrochemical Characterisationmentioning
confidence: 99%
“…The measured EIS spectra were averaged from three cells aer normalisation. 73,77 In Fig. 4a, Nyquist plots of CB and CB] O (72 h) cathodes are shown at different applied potentials during charging and discharging.…”
Section: Electrochemical Characterisationmentioning
confidence: 99%
“…Amin et al [28] found that the electronic conductivity of NMC111 varies between 10 À 6 S m À 1 and 10 0 S m À 1 depending on lithiation and temperature. Furthermore, results from Kuo et al [29] suggested that measuring the electronic conductivity of NMC111 is difficult and includes uncertainties. For this reason, we chose a range of 10 À 6 S m À 1 to 10 À 2 S m À 1 for studying the qualitative influence of electronic conductivity on the cell performance.…”
Section: Interplay Between Secondary Particle Porosity and Electronic...mentioning
confidence: 99%